Perovskite solar cell based on potassium chlorate interlayer modification

By introducing a potassium chlorate interlayer between the transparent conductive glass and the NiOx hole transport layer, oxygen and potassium chloride are generated, the crystallinity and conductivity of NiOx are improved, the problem of low crystallinity of NiOx film is solved, and the photoelectric conversion efficiency and stability of perovskite solar cells are improved.

CN120692991APending Publication Date: 2025-09-23HEFEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510866044.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-26
Publication Date
2025-09-23

AI Technical Summary

Technical Problem

The magnetron sputtered NiOx film has low crystallinity and defects, resulting in insufficient hole extraction at the perovskite/hole transport layer interface, affecting the photoelectric conversion efficiency and stability of the battery.

Method used

A potassium chlorate (KClO3) interlayer is introduced between the transparent conductive glass and the NiOx hole transport layer. Oxygen and potassium chloride are generated through high-temperature annealing to improve the crystallinity and conductivity of NiOx and optimize the Ni3+/Ni2+ ratio.

Benefits of technology

The photoelectric conversion efficiency and light stability of perovskite solar cells are improved, and the problems of low crystallinity and defects in NiOx films are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120692991A_ABST
    Figure CN120692991A_ABST
Patent Text Reader

Abstract

The invention discloses a perovskite solar cell based on potassium chlorate interlayer modification, and belongs to the field of perovskite solar cells. According to the invention, the potassium chlorate intermediate layer is introduced between the transparent conductive substrate and the NiOx hole transport layer, so that the problems of low crystallinity and many defects of the NiOx film caused by magnetron sputtering are solved, O2 generated by decomposition of potassium chlorate can help to improve the ratio of Ni < 3 + > / Ni < 2 + >, the conductivity of NiOx is improved, and the performance of the NiOx film is improved. Therefore, the perovskite solar cell shows excellent photoelectric conversion efficiency. The method is simple in process and compatible with large-area preparation, and a new strategy is provided for efficient and stable perovskite solar cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of perovskite solar cells, and in particular relates to a perovskite solar cell based on a potassium chlorate intermediate layer modification. Background Art

[0002] In recent years, with economic development and a growing global population, the demand for energy has been increasing year by year. Currently, fossil fuels are still the most widely used energy source for daily activities. Conventional fossil fuels are non-renewable energy sources. For a long time, my country's fossil energy, and indeed the world's, has been used endlessly. Current reserves are severely insufficient, making it difficult to meet people's production and daily needs. The demand for renewable energy is increasing, making the search and development of new, clean energy sources a critical task for countries around the world. Among the many renewable energy sources, solar energy holds the greatest potential for development, and solar cells are a primary means of converting solar energy into electricity. In recent years, organic-inorganic hybrid perovskite structures have attracted considerable research interest due to their advantages, including strong light absorption, long charge carrier lifetime, high carrier mobility, long carrier diffusion distances, and low cost. Researchers have focused on perovskite solar cells based on these materials. In particular, inverted perovskite solar cells have garnered particular attention due to their ease of fabrication.

[0003] Current magnetron sputtered NiOx films often result in low crystallinity and defects, which impair the conductivity of the film. The complex chemical surface properties and insufficient Ni 3+ / Ni 2+ The ratio affects the hole extraction at the perovskite / hole transport layer interface, resulting in low photoelectric conversion efficiency and poor stability of the battery. Summary of the Invention

[0004] The present invention addresses the problems of the above-mentioned prior art and provides a perovskite solar cell based on potassium chlorate intermediate layer modification. The present invention introduces a strong oxidant potassium chlorate (KClO3) intermediate layer between the transparent conductive glass (TCO) and the NiOx hole transport layer, thereby improving the crystallinity of NiOx and passivating the defects of NiOx. The O2 generated by the decomposition of potassium chlorate can help improve the NiOx 3+ / Ni 2+ The ratio of NiOx to NiOx improves the conductivity of NiOx, making the perovskite solar cell exhibit excellent photoelectric conversion efficiency and light stability.

[0005] The present invention is based on a perovskite solar cell modified with a potassium chlorate intermediate layer, in which an intermediate layer is provided between a transparent conductive substrate and a hole transport layer, wherein the intermediate layer is obtained by spin coating a KClO3 aqueous solution and annealing at a high temperature.

[0006] The concentration of the KClO3 aqueous solution is 5-15 mg / mL.

[0007] The specific steps include:

[0008] A KClO3 aqueous solution was spin-coated on the pretreated transparent conductive substrate, followed by magnetron sputtering deposition of NiO x The hole transport layer is sputtered and then annealed at high temperature. The perovskite light absorption layer, electron transport layer, and metal electrode are then prepared in sequence using conventional methods.

[0009] Furthermore, when the KClO 3 aqueous solution was spin-coated, the spin-coating speed was 4000 rpm and the spin-coating time was 40 s.

[0010] Furthermore, NiO was deposited by magnetron sputtering. x For the hole transport layer, the sputtering power was 85 W, the sputtering pressure was 0.5 Pa, and the argon gas flow rate was 50 sccm.

[0011] Furthermore, the high temperature annealing temperature is 400° C., and the annealing time is 20 min.

[0012] The perovskite solar cell is of PIN type, and its structure from bottom to top is sequentially arranged as a transparent conductive substrate, a p-type hole transport layer, a perovskite light absorption layer, an n-type electron transport layer and a metal electrode.

[0013] Furthermore, a self-assembled monolayer (SAM) is provided between the p-type hole transport layer and the perovskite light absorbing layer.

[0014] Furthermore, a passivation layer is provided between the perovskite light absorbing layer and the n-type electron transport layer.

[0015] Furthermore, 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) is provided as a buffer layer between the n-type electron transport layer and the metal electrode.

[0016] Specifically, in the pin structure:

[0017] The transparent conductive substrate is indium tin oxide (ITO) or fluorine-doped indium tin oxide (FTO), but is not limited to the above.

[0018] The p-type hole transport layer can be prepared using one or more p-type semiconductor materials selected from NiOx (NiO), molybdenum oxide (MoO3), cuprous oxide (Cu2O), copper iodide (CuI), copper phthalocyanine (CuPc), cuprous thiocyanate (CuSCN), redox graphene, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), poly(3,4-ethylenedioxythiophene:polystyrenesulfonate) (PEDOT:PSS), 4-butyl-N,N-diphenylaniline homopolymer (PolyTPD), polyvinylcarbazole (PVK), etc., but is not limited to the p-type semiconductor materials listed above.

[0019] The self-assembled monolayer (SAM) can be prepared using one or more materials selected from the group consisting of [4-(3,6-dimethyl-9H-carbazol-9-yl)butyl]phosphonic acid (Me-4PACz), [2-(3,6-dimethoxy-9H-carbazol-9-yl)ethyl]phosphonic acid (Meo-2PACz), (4-(3,6-di-tert-butyl-9H-carbazol-9-yl)butyl)phosphonic acid (tBu-4PACz), and 2-(3,6-dimethyl-9H-carbazol-9-yl)ethylphosphonic acid (Me-2PACz), but is not limited to the materials listed above.

[0020] The perovskite light absorbing layer is ABX3, where A is FA + 、MA + 、Cs + Any one or more of the following, B is Pb 2+ , X is I ﹣ 、Cl ﹣ Br ﹣ Any one or more of the .

[0021] The n-type electron transport layer can be made of titanium oxide (TiO2), tin oxide (SnO2), zinc oxide (ZnO), fullerene (C 60 ), graphene, fullerene derivative [6,6]-phenyl-C61-butyric acid methyl ester (PC 61 BM) etc., but is not limited to the n-type semiconductor materials listed above.

[0022] The passivation layer can be prepared from one or more materials selected from the group consisting of phenylethylammonium iodide (PEAI), phenylethylammonium bromide (PEABr), phenylethylammonium chloride (PEACl), 4-tert-butylbenzoic acid methyl ester iodide (tBBAI), and phenylpropylammonium iodide (PPAI), but is not limited to the materials listed above.

[0023] The metal electrodes are gold (Au), silver (Ag), copper (Cu), etc., but are not limited to the metal electrodes listed above.

[0024] Taking the inverted structure (pin) perovskite thin film solar cell as an example, the preparation steps are as follows:

[0025] Step 1: Ultrasonic clean the transparent conductive glass using detergent, ultrapure water, and anhydrous ethanol. Afterwards, dry the cleaned transparent conductive glass with nitrogen and place it in a UV-ozone device for 5-20 minutes to improve its wettability.

[0026] Step 2: Spin coat a layer of KClO₃ aqueous solution on the conductive glass treated in step 1. Dissolve 10 mg of KClO₃ in 1 ml of ultrapure water and spin coat the treated conductive glass for 40 seconds at 4000 rpm.

[0027] Step 3: Preparation of hole transport layer: Deposition of 10 nm NiO by magnetron sputtering x The film was deposited at a sputtering power of 85 W, a sputtering pressure of 0.5 Pa, and an argon gas flow rate of 50 sccm. After preparation, the sample was placed on a heating stage and annealed at 400°C for 20 min.

[0028] Step 4: Dissolve 1 mg of Me-4PACz in 1 ml of ethanol and spin-coat the hole-transport layer obtained in Step 3 for 30 seconds at 4000 rpm. After spin coating, place the sample on a heating plate and anneal at 100°C for 5 minutes.

[0029] Step 5: Based on the process of Step 4, a perovskite film was deposited by dissolving 691 mg of PbI2, 19 mg of CsI, 219 mg of FAI, and 23 mg of MAI in 1 ml of a mixed solvent (DMF:DMSO = 4:1). The solution was spin-coated in a nitrogen glove box at 5000 rpm for 45 seconds, with a 5-second acceleration time. After 27 seconds of spin, 200 μl of chlorobenzene was added as an antisolvent. The film was then annealed at 115°C for 15 minutes.

[0030] Step 6: Passivation layer preparation: Dissolve 1 mg of PEABr in 1 ml of isopropanol and dynamically spin-coat the perovskite film for 30 seconds at 6000 rpm. After spin-coating, place the sample on a hot plate and anneal at 100°C for 5 minutes.

[0031] Step 7: Preparation of electron transport layer: 10 mg PC 61BM was dissolved in 1 ml of chlorobenzene and spin-coated onto the passivation layer for 30 seconds at 4000 rpm. After spin-coating, the layer was annealed on a 100°C heating plate for 10 minutes to form the electron transport layer.

[0032] Step 8: Dissolve 1 mg of BCP in 1 ml of isopropanol and spin coat the electron transport layer at a speed of 6000 rpm for 30 s. After spin coating, anneal the layer on a heating plate at 100 °C for 10 min.

[0033] Step 9: Finally, use an evaporation device to evaporate a layer of 100nm thick Ag as the back electrode at a rate of 0.5 Å / s using silver as the thermal evaporation source.

[0034] In step 9, the metal electrode includes gold, silver, copper, etc.

[0035] A perovskite solar cell is prepared by the preparation method described in steps 1-9.

[0036] The present invention has the following beneficial effects:

[0037] The present invention introduces a layer of KClO3 between the TCO and the sputtered NiOx layer. Through high temperature annealing (above 400°C), KClO3 can undergo thermal decomposition reaction to generate oxygen (O2) and potassium chloride (KCl). The advantages of this process are: 1. The decomposed O2 can help improve the Ni 3+ / Ni 2+ 2. During the high vacuum process of magnetron sputtering NiOx, oxygen vacancies often lead to a decrease in electrical performance. The O2 generated by the decomposition of KClO3 can fill oxygen vacancies and optimize carrier mobility. 3. The generated KCl acts as an interface modification layer, helping to improve the crystallinity of NiOx. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The accompanying drawings related to the technical solution are described as follows: To clearly illustrate the technical features of the embodiments of the present invention and the prior art solutions, the following diagrams and files related to the specific implementation methods are listed. It should be noted that the drawings contained in this document are only representative implementation examples of the present invention. Those skilled in the relevant art can deduce other implementation diagrams based on the illustrated examples without inventive work, provided that they fully understand the technical key points of the present invention.

[0039] Figure 1 Schematic diagram of the perovskite battery structure (pin structure) in the present invention.

[0040] Figure 2 This is a surface SEM of an ITO substrate and a layer of potassium chlorate deposited on the ITO in the present invention.

[0041] Figure 3 This is the XRD curve of the present invention using ITO as a substrate and depositing a layer of potassium chlorate on the ITO.

[0042] Figure 4 NiO obtained in Comparative Example 1 and Example 2 of the present invention x XRD curve of the film.

[0043] Figure 5 NiO obtained in Comparative Example 1 and Example 2 of the present invention x Surface SEM of the film.

[0044] Figure 6 JV characteristic curves of the wide bandgap perovskite solar cells obtained in Comparative Example 1 and Example 2 of the present invention tested under AM 1.5 sunlight.

[0045] Figure 7 JV characteristic curves of the wide bandgap perovskite solar cells obtained in Comparative Example 2 and Example 6 of the present invention tested under AM 1.5 sunlight. DETAILED DESCRIPTION

[0046] The present invention discloses a perovskite solar cell based on TCO / NiOx hole transport layer interface modification. The present invention introduces a layer of KClO3 between the TCO and the sputtered NiOx layer, and through high temperature annealing, causes the KClO3 to undergo a thermal decomposition reaction to generate O2 and KCl, thereby solving the problem that magnetron sputtered NiOx films usually have low film crystallinity and many defects, and the complex chemical surface properties and insufficient Ni 3+ / Ni 2+ The ratio affects the hole extraction at the perovskite / hole transport layer interface, resulting in low photoelectric conversion efficiency and poor stability of the battery.

[0047] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process. However, the protection scope of the present invention is not limited to the following embodiment.

[0048] Comparative Example 1:

[0049] This comparative example is a small-area perovskite solar cell, and its preparation process and steps are as follows:

[0050] (1) Select an ITO substrate of 1.5 cm × 1.5 cm and place it in detergent, deionized water, isopropyl alcohol, and anhydrous ethanol in turn for ultrasonic treatment for 15 minutes, place it in a 60 °C oven for drying, and then place the cleaned conductive glass substrate in a UV-ozone device for treatment for 40 minutes.

[0051] (2) Preparation of hole transport layer: 10 nm NiO was deposited by magnetron sputtering under the following parameters: x Thin film: Sputtering power 85W, sputtering pressure 0.5 Pa, argon gas flow rate 50 sccm. After preparation, the sample was placed on a heating stage and annealed at 400°C for 20 min.

[0052] (3) Dissolve 1 mg of Me-4PACz in 1 ml of ethanol and spin-coat it onto the treated hole transport layer. The spin-coating time is 30 s and the speed is 4000 rpm. After spin-coating, place the sample on a heating stage and anneal at 100 °C for 5 min.

[0053] (4) Based on the previous step, a perovskite film was deposited by dissolving 691 mg of PbI2, 19 mg of CsI, 219 mg of FAI, and 23 mg of MAI in 1 ml of a mixed solvent (DMF:DMSO = 4:1). The solution was spin-coated in a nitrogen glove box at 5000 rpm for 45 s, with an acceleration time of 5 s. After 27 s of rotation, 200 μl of chlorobenzene was added as an antisolvent, and then annealed at 115 °C for 15 min.

[0054] (5) Preparation of the passivation layer: 1 mg of PEABr was dissolved in 1 ml of isopropanol and dynamically spin-coated onto the perovskite film. The spin-coating time was 30 s and the rotation speed was 6000 rpm. After spin-coating, the sample was placed on a heating stage and annealed at 100 °C for 5 min.

[0055] (6) Preparation of electron transport layer: 10 mg PC 61 BM was dissolved in 1 ml of chlorobenzene and spin-coated onto the passivation layer for 30 seconds at 4000 rpm. After spin coating, the layer was annealed on a 100°C heating plate for 10 minutes to form the electron transport layer.

[0056] (7) Dissolve 1 mg of BCP in 1 ml of isopropanol and spin-coat it onto the electron transport layer. The spin-coating time is 30 s and the speed is 6000 rpm. After spin-coating, anneal it on a heating plate at 100 °C for 10 min.

[0057] (8) Finally, a 100 nm thick layer of Ag was deposited as the back electrode using an evaporation apparatus with silver as the thermal evaporation source at a rate of 0.5 Å / s.

[0058] Steps (1)-(8) are conventional methods for preparing small-area perovskite solar cells.

[0059] Comparative Example 2:

[0060] This comparative example is a small-area perovskite solar cell, and its preparation process and steps are as follows:

[0061] (1) Select a 1.5 cm × 1.5 cm FTO substrate and place it in detergent, deionized water, isopropyl alcohol, and anhydrous ethanol in turn for ultrasonic treatment for 15 minutes, then place it in a 60 ° C oven for drying, and then place the cleaned conductive glass substrate in a UV-ozone device for 40 minutes.

[0062] (2) Preparation of hole transport layer: 10 nm NiO was deposited by magnetron sputtering under the following parameters: x Thin film: Sputtering power 85W, sputtering pressure 0.5 Pa, argon gas flow rate 50 sccm. After preparation, the sample was placed on a heating stage and annealed at 400°C for 20 min.

[0063] (3) Dissolve 1 mg of Me-4PACz in 1 ml of ethanol and spin-coat it onto the treated hole transport layer. The spin-coating time is 30 s and the speed is 4000 rpm. After spin-coating, place the sample on a heating stage and anneal at 100 °C for 5 min.

[0064] (4) Based on the previous step, a perovskite film was deposited by dissolving 691 mg of PbI2, 19 mg of CsI, 219 mg of FAI, and 23 mg of MAI in 1 ml of a mixed solvent (DMF:DMSO = 4:1). The solution was spin-coated in a nitrogen glove box at 5000 rpm for 45 s, with an acceleration time of 5 s. After 27 s of rotation, 200 μl of chlorobenzene was added as an antisolvent, and then annealed at 115 °C for 15 min.

[0065] (5) Preparation of the passivation layer: 1 mg of PEABr was dissolved in 1 ml of isopropanol and dynamically spin-coated onto the perovskite film. The spin-coating time was 30 s and the rotation speed was 6000 rpm. After spin-coating, the sample was placed on a heating stage and annealed at 100 °C for 5 min.

[0066] (6) Preparation of electron transport layer: 10 mg PC 61 BM was dissolved in 1 ml of chlorobenzene and spin-coated onto the passivation layer for 30 seconds at 4000 rpm. After spin-coating, the layer was annealed on a heating plate at 100°C for 10 minutes to form the electron transport layer.

[0067] (7) Dissolve 1 mg of BCP in 1 ml of isopropanol and spin-coat it onto the electron transport layer. The spin-coating time is 30 s and the speed is 6000 rpm. After spin-coating, anneal it on a heating plate at 100 °C for 10 min.

[0068] (8) Finally, a 100 nm thick layer of Ag was deposited as the back electrode using an evaporation apparatus with silver as the thermal evaporation source at a rate of 0.5 Å / s.

[0069] Steps (1)-(8) are conventional methods for preparing small-area perovskite solar cells.

[0070] Example 1:

[0071] The perovskite solar cell based on TCO / NiOx hole transport layer interface modification in this embodiment is prepared in the following process and steps:

[0072] (1) Select an ITO substrate of 1.5 cm × 1.5 cm and place it in detergent, deionized water, isopropyl alcohol, and anhydrous ethanol in turn for ultrasonic treatment for 15 minutes, place it in a 60 °C oven for drying, and then place the cleaned conductive glass substrate in a UV-ozone device for treatment for 40 minutes.

[0073] (2) Spin-coat a layer of KClO₃ aqueous solution on the treated conductive glass. Dissolve 5 mg of KClO₃ in 1 ml of ultrapure water and spin-coat it on the treated conductive glass. The spin-coating time is 40 s and the rotation speed is 4000 rpm.

[0074] (3) Preparation of hole transport layer: 10 nm NiO was deposited by magnetron sputtering under the following parameters: x Thin films were prepared using a sputtering power of 85 W, a sputtering pressure of 0.5 Pa, and an argon flow rate of 50 sccm. After preparation, the sample was placed on a heating stage and annealed at 400 °C for 20 min.

[0075] (4) Dissolve 1 mg of Me-4PACz in 1 ml of ethanol and spin-coat it onto the treated hole transport layer. The spin-coating time is 30 s and the speed is 4000 rpm. After spin-coating, place the sample on a heating stage and anneal at 100 °C for 5 min.

[0076] (5) Based on the previous step, a perovskite film was deposited by dissolving 691 mg of PbI2, 19 mg of CsI, 219 mg of FAI, and 23 mg of MAI in 1 ml of a mixed solvent (DMF:DMSO = 4:1). The solution was spin-coated in a nitrogen glove box at 5000 rpm for 45 s, with an acceleration time of 5 s. After 27 s of rotation, 200 μl of chlorobenzene was added as an antisolvent, and then annealed at 115 °C for 15 min.

[0077] (6) Preparation of the passivation layer: 1 mg of PEABr was dissolved in 1 ml of isopropanol and dynamically spin-coated onto the perovskite film. The spin-coating time was 30 s and the rotation speed was 6000 rpm. After spin-coating, the sample was placed on a heating stage and annealed at 100 °C for 5 min.

[0078] (7) Preparation of electron transport layer: 10 mg PC 61 BM was dissolved in 1 ml of chlorobenzene and spin-coated onto the passivation layer for 30 seconds at 4000 rpm. After spin coating, the layer was annealed on a 100°C heating plate for 10 minutes to form the electron transport layer.

[0079] (8) Dissolve 1 mg of BCP in 1 ml of isopropanol and spin-coat it onto the electron transport layer. The spin-coating time is 30 s and the speed is 6000 rpm. After spin-coating, anneal it on a heating plate at 100 °C for 10 min.

[0080] (9) Finally, a 100 nm thick layer of Ag was deposited as the back electrode using an evaporation apparatus with silver as the thermal evaporation source at a rate of 0.5 Å / s.

[0081] The preparation method of steps (1)-(9) obtains a small-area perovskite solar cell based on an ITO / NiOx hole transport layer structure modified with a potassium chlorate intermediate layer.

[0082] Example 2:

[0083] The perovskite solar cell based on TCO / NiOx hole transport layer interface modification in this embodiment is prepared in the following process and steps:

[0084] (1) Select an ITO substrate of 1.5 cm × 1.5 cm and place it in detergent, deionized water, isopropyl alcohol, and anhydrous ethanol in turn for ultrasonic treatment for 15 minutes, place it in a 60 °C oven for drying, and then place the cleaned conductive glass substrate in a UV-ozone device for treatment for 40 minutes.

[0085] (2) Spin-coat a layer of KClO₃ aqueous solution on the treated conductive glass. Dissolve 10 mg of KClO₃ in 1 ml of ultrapure water and spin-coat it on the treated conductive glass. The spin-coating time is 40 s and the speed is 4000 rpm.

[0086] (3) Preparation of hole transport layer: 10 nm NiO was deposited by magnetron sputtering under the following parameters: x Thin films were prepared using a sputtering power of 85 W, a sputtering pressure of 0.5 Pa, and an argon flow rate of 50 sccm. After preparation, the sample was placed on a heating stage and annealed at 400 °C for 20 min.

[0087] (4) Dissolve 1 mg of Me-4PACz in 1 ml of ethanol and spin-coat it onto the treated hole transport layer. The spin-coating time is 30 s and the speed is 4000 rpm. After spin-coating, place the sample on a heating stage and anneal at 100 °C for 5 min.

[0088] (5) Based on the previous step, a perovskite film was deposited by dissolving 691 mg of PbI2, 19 mg of CsI, 219 mg of FAI, and 23 mg of MAI in 1 ml of a mixed solvent (DMF:DMSO = 4:1). The solution was spin-coated in a nitrogen glove box at 5000 rpm for 45 s, with an acceleration time of 5 s. After 27 s of rotation, 200 μl of chlorobenzene was added as an antisolvent, and then annealed at 115 °C for 15 min.

[0089] (6) Preparation of the passivation layer: 1 mg of PEABr was dissolved in 1 ml of isopropanol and dynamically spin-coated onto the perovskite film. The spin-coating time was 30 s and the rotation speed was 6000 rpm. After spin-coating, the sample was placed on a heating stage and annealed at 100 °C for 5 min.

[0090] (7) Preparation of electron transport layer: 10 mg PC 61 BM was dissolved in 1 ml of chlorobenzene and spin-coated onto the passivation layer for 30 seconds at 4000 rpm. After spin coating, the layer was annealed on a 100°C heating plate for 10 minutes to form the electron transport layer.

[0091] (8) Dissolve 1 mg of BCP in 1 ml of isopropanol and spin-coat it onto the electron transport layer. The spin-coating time is 30 s and the speed is 6000 rpm. After spin-coating, anneal it on a heating plate at 100°C for 10 min.

[0092] (9) Finally, a 100 nm thick layer of Ag was deposited as the back electrode using an evaporation apparatus with silver as the thermal evaporation source at a rate of 0.5 Å / s.

[0093] The preparation method of steps (1)-(9) obtains a small-area perovskite solar cell based on an ITO / NiOx hole transport layer structure modified with a potassium chlorate intermediate layer.

[0094] Example 3:

[0095] The perovskite solar cell based on TCO / NiOx hole transport layer interface modification in this embodiment is prepared in the following process and steps:

[0096] (1) Select an ITO substrate of 1.5 cm × 1.5 cm and place it in detergent, deionized water, isopropyl alcohol, and anhydrous ethanol in turn for ultrasonic treatment for 15 minutes, place it in a 60 °C oven for drying, and then place the cleaned conductive glass substrate in a UV-ozone device for treatment for 40 minutes.

[0097] (2) Spin-coat a layer of KClO3 aqueous solution on the treated conductive glass. Dissolve 15 mg of KClO3 in 1 ml of ultrapure water and spin-coat it on the treated conductive glass. The spin-coating time is 40 s and the speed is 4000 rpm.

[0098] (3) Preparation of hole transport layer: 10 nm NiO was deposited by magnetron sputtering under the following parameters: x Thin films were prepared using a sputtering power of 85 W, a sputtering pressure of 0.5 Pa, and an argon flow rate of 50 sccm. After preparation, the sample was placed on a heating stage and annealed at 400 °C for 20 min.

[0099] (4) Dissolve 1 mg of Me-4PACz in 1 ml of ethanol and spin-coat it onto the treated hole transport layer. The spin-coating time is 30 s and the speed is 4000 rpm. After spin-coating, place the sample on a heating stage and anneal at 100 °C for 5 min.

[0100] (5) Based on the previous step, a perovskite film was deposited by dissolving 691 mg of PbI2, 19 mg of CsI, 219 mg of FAI, and 23 mg of MAI in 1 ml of a mixed solvent (DMF:DMSO = 4:1). The solution was spin-coated in a nitrogen glove box at 5000 rpm for 45 s, with an acceleration time of 5 s. After 27 s of rotation, 200 μl of chlorobenzene was added as an antisolvent, and then annealed at 115 °C for 15 min.

[0101] (6) Preparation of the passivation layer: 1 mg of PEABr was dissolved in 1 ml of isopropanol and dynamically spin-coated onto the perovskite film. The spin-coating time was 30 s and the rotation speed was 6000 rpm. After spin-coating, the sample was placed on a heating stage and annealed at 100 °C for 5 min.

[0102] (7) Preparation of electron transport layer: 10 mg PC 61 BM was dissolved in 1 ml of chlorobenzene and spin-coated onto the passivation layer for 30 seconds at 4000 rpm. After spin coating, the layer was annealed on a 100°C heating plate for 10 minutes to form the electron transport layer.

[0103] (8) Dissolve 1 mg of BCP in 1 ml of isopropanol and spin-coat it onto the electron transport layer. The spin-coating time is 30 s and the speed is 6000 rpm. After spin-coating, anneal it on a heating plate at 100 °C for 10 min.

[0104] (9) Finally, a 100 nm thick layer of Ag was deposited as the back electrode using an evaporation apparatus with silver as the thermal evaporation source at a rate of 0.5 Å / s.

[0105] The preparation method of steps (1)-(9) obtains a small-area perovskite solar cell based on an ITO / NiOx hole transport layer structure modified with a potassium chlorate intermediate layer.

[0106] Example 4:

[0107] The perovskite solar cell based on TCO / NiOx hole transport layer interface modification in this embodiment is prepared in the following process and steps:

[0108] (1) Select an ITO substrate of 1.5 cm × 1.5 cm and place it in detergent, deionized water, isopropyl alcohol, and anhydrous ethanol in turn for ultrasonic treatment for 15 minutes, place it in a 60 °C oven for drying, and then place the cleaned conductive glass substrate in a UV-ozone device for treatment for 40 minutes.

[0109] (2) Preparation of hole transport layer: 10 nm NiO was deposited by magnetron sputtering under the following parameters: x Thin film: Sputtering power 85W, sputtering pressure 0.5 Pa, argon flow rate 50 sccm. A layer of KClO₃ aqueous solution was spin-coated on the treated conductive glass. Dissolve 10 mg of KClO₃ in 1 ml of ultrapure water and spin-coat the treated conductive glass for 40 seconds at 4000 rpm. After spin coating, place the sample on a hot plate and anneal at 100°C for 5 minutes.

[0110] (3) Spin-coat a layer of KClO₃ aqueous solution onto the hole transport layer. Dissolve 10 mg of KClO₃ in 1 ml of ultrapure water and spin-coat it onto the treated hole transport layer for 40 seconds at a speed of 4000 rpm. After spin coating, place the sample on a heating stage and anneal at 400°C for 5 minutes.

[0111] (4) Dissolve 1 mg of Me-4PACz in 1 ml of ethanol and spin-coat it onto the treated KClO3 for 30 s at 4000 rpm. After spin-coating, place the sample on a heating stage and anneal at 100 °C for 5 min.

[0112] (5) Based on the previous step, a perovskite film was deposited by dissolving 691 mg of PbI2, 19 mg of CsI, 219 mg of FAI, and 23 mg of MAI in 1 ml of a mixed solvent (DMF:DMSO = 4:1). The solution was spin-coated in a nitrogen glove box at 5000 rpm for 45 s, with an acceleration time of 5 s. After 27 s of rotation, 200 μl of chlorobenzene was added as an antisolvent, and then annealed at 115 °C for 15 min.

[0113] (6) Preparation of the passivation layer: 1 mg of PEABr was dissolved in 1 ml of isopropanol and dynamically spin-coated onto the perovskite film. The spin-coating time was 30 s and the rotation speed was 6000 rpm. After spin-coating, the sample was placed on a heating stage and annealed at 100 °C for 5 min.

[0114] (7) Preparation of electron transport layer: 10 mg PC 61 BM was dissolved in 1 ml of chlorobenzene and spin-coated onto the passivation layer for 30 seconds at 4000 rpm. After spin coating, the layer was annealed on a 100°C heating plate for 10 minutes to form the electron transport layer.

[0115] (8) Dissolve 1 mg of BCP in 1 ml of isopropanol and spin-coat it onto the electron transport layer. The spin-coating time is 30 s and the speed is 6000 rpm. After spin-coating, anneal it on a heating plate at 100 °C for 10 min.

[0116] (9) Finally, a 100 nm thick layer of Ag was deposited as the back electrode using an evaporation apparatus with silver as the thermal evaporation source at a rate of 0.5 Å / s.

[0117] The preparation method of steps (1)-(9) obtains a small-area perovskite solar cell based on an ITO / NiOx hole transport layer structure modified with a potassium chlorate intermediate layer.

[0118] Example 5:

[0119] The perovskite solar cell based on TCO / NiOx hole transport layer interface modification in this embodiment is prepared in the following process and steps:

[0120] (1) Select a 1.5 cm × 1.5 cm FTO substrate and place it in detergent, deionized water, isopropyl alcohol, and anhydrous ethanol in turn for ultrasonic treatment for 15 minutes, then place it in a 60 ° C oven for drying, and then place the cleaned conductive glass substrate in a UV-ozone device for 40 minutes.

[0121] (2) Spin-coat a layer of KClO₃ aqueous solution on the treated conductive glass. Dissolve 5 mg of KClO₃ in 1 ml of ultrapure water and spin-coat it on the treated conductive glass. The spin-coating time is 40 s and the rotation speed is 4000 rpm.

[0122] (3) Preparation of hole transport layer: 10 nm NiO was deposited by magnetron sputtering under the following parameters: x Thin films were prepared using a sputtering power of 85 W, a sputtering pressure of 0.5 Pa, and an argon flow rate of 50 sccm. After preparation, the sample was placed on a heating stage and annealed at 400 °C for 20 min.

[0123] (4) Dissolve 1 mg of Me-4PACz in 1 ml of ethanol and spin-coat it onto the treated hole transport layer. The spin-coating time is 30 s and the speed is 4000 rpm. After spin-coating, place the sample on a heating stage and anneal at 100 °C for 5 min.

[0124] (5) Based on the previous step, a perovskite film was deposited by dissolving 691 mg of PbI2, 19 mg of CsI, 219 mg of FAI, and 23 mg of MAI in 1 ml of a mixed solvent (DMF:DMSO = 4:1). The solution was spin-coated in a nitrogen glove box at 5000 rpm for 45 s, with an acceleration time of 5 s. After 27 s of rotation, 200 μl of chlorobenzene was added as an antisolvent, and then annealed at 115 °C for 15 min.

[0125] (6) Preparation of the passivation layer: 1 mg of PEABr was dissolved in 1 ml of isopropanol and dynamically spin-coated onto the perovskite film. The spin-coating time was 30 s and the rotation speed was 6000 rpm. After spin-coating, the sample was placed on a heating stage and annealed at 100 °C for 5 min.

[0126] (7) Preparation of electron transport layer: 10 mg PC 61 BM was dissolved in 1 ml of chlorobenzene and spin-coated onto the passivation layer for 30 seconds at 4000 rpm. After spin coating, the layer was annealed on a 100°C heating plate for 10 minutes to form the electron transport layer.

[0127] (8) Dissolve 1 mg of BCP in 1 ml of isopropanol and spin-coat it onto the electron transport layer. The spin-coating time is 30 s and the speed is 6000 rpm. After spin-coating, anneal it on a heating plate at 100 °C for 10 min.

[0128] (9) Finally, a 100 nm thick layer of Ag was deposited as the back electrode using an evaporation apparatus with silver as the thermal evaporation source at a rate of 0.5 Å / s.

[0129] The preparation method of steps (1)-(9) obtains a small-area perovskite solar cell based on an ITO / NiOx hole transport layer structure modified with a potassium chlorate intermediate layer.

[0130] Example 6:

[0131] The perovskite solar cell based on TCO / NiOx hole transport layer interface modification in this embodiment is prepared in the following process and steps:

[0132] (1) Select a 1.5 cm × 1.5 cm FTO substrate and place it in detergent, deionized water, isopropyl alcohol, and anhydrous ethanol in turn for ultrasonic treatment for 15 minutes, then place it in a 60 ° C oven for drying, and then place the cleaned conductive glass substrate in a UV-ozone device for 40 minutes.

[0133] (2) Spin-coat a layer of KClO₃ aqueous solution on the treated conductive glass. Dissolve 10 mg of KClO₃ in 1 ml of ultrapure water and spin-coat it on the treated conductive glass. The spin-coating time is 40 s and the speed is 4000 rpm.

[0134] (3) Preparation of hole transport layer: 10 nm NiO was deposited by magnetron sputtering under the following parameters: x Thin films were prepared using a sputtering power of 85 W, a sputtering pressure of 0.5 Pa, and an argon flow rate of 50 sccm. After preparation, the sample was placed on a heating stage and annealed at 400 °C for 20 min.

[0135] (4) Dissolve 1 mg of Me-4PACz in 1 ml of ethanol and spin-coat it onto the treated hole transport layer. The spin-coating time is 30 s and the speed is 4000 rpm. After spin-coating, place the sample on a heating stage and anneal at 100 °C for 5 min.

[0136] (5) Based on the previous step, a perovskite film was deposited by dissolving 691 mg of PbI2, 19 mg of CsI, 219 mg of FAI, and 23 mg of MAI in 1 ml of a mixed solvent (DMF:DMSO = 4:1). The solution was spin-coated in a nitrogen glove box at 5000 rpm for 45 s, with an acceleration time of 5 s. After 27 s of rotation, 200 μl of chlorobenzene was added as an antisolvent, and then annealed at 115 °C for 15 min.

[0137] (6) Preparation of the passivation layer: 1 mg of PEABr was dissolved in 1 ml of isopropanol and dynamically spin-coated onto the perovskite film. The spin-coating time was 30 s and the rotation speed was 6000 rpm. After spin-coating, the sample was placed on a heating stage and annealed at 100 °C for 5 min.

[0138] (7) Preparation of electron transport layer: 10 mg PC 61 BM was dissolved in 1 ml of chlorobenzene and spin-coated onto the passivation layer for 30 seconds at 4000 rpm. After spin coating, the layer was annealed on a 100°C heating plate for 10 minutes to form the electron transport layer.

[0139] (8) Dissolve 1 mg of BCP in 1 ml of isopropanol and spin-coat it onto the electron transport layer. The spin-coating time is 30 s and the speed is 6000 rpm. After spin-coating, anneal it on a heating plate at 100 °C for 10 min.

[0140] (9) Finally, a 100 nm thick layer of Ag was deposited as the back electrode using an evaporation apparatus with silver as the thermal evaporation source at a rate of 0.5 Å / s.

[0141] The preparation method of steps (1)-(9) obtains a small-area perovskite solar cell based on an ITO / NiOx hole transport layer structure modified with a potassium chlorate intermediate layer.

[0142] Example 7:

[0143] The perovskite solar cell based on TCO / NiOx hole transport layer interface modification in this embodiment is prepared in the following process and steps:

[0144] (1) Select a 1.5 cm × 1.5 cm FTO substrate and place it in detergent, deionized water, isopropyl alcohol, and anhydrous ethanol in turn for ultrasonic treatment for 15 minutes, then place it in a 60 ° C oven for drying, and then place the cleaned conductive glass substrate in a UV-ozone device for 40 minutes.

[0145] (2) Spin-coat a layer of KClO3 aqueous solution on the treated conductive glass. Dissolve 15 mg of KClO3 in 1 ml of ultrapure water and spin-coat it on the treated conductive glass. The spin-coating time is 40 s and the speed is 4000 rpm.

[0146] (3) Preparation of hole transport layer: 10 nm NiO was deposited by magnetron sputtering under the following parameters: x Thin films were prepared using a sputtering power of 85 W, a sputtering pressure of 0.5 Pa, and an argon flow rate of 50 sccm. After preparation, the sample was placed on a heating stage and annealed at 400°C for 20 min.

[0147] (4) Dissolve 1 mg of Me-4PACz in 1 ml of ethanol and spin-coat it onto the treated hole transport layer. The spin-coating time is 30 s and the speed is 4000 rpm. After spin-coating, place the sample on a heating stage and anneal at 100 °C for 5 min.

[0148] (5) Based on the previous step, a perovskite film was deposited by dissolving 691 mg of PbI2, 19 mg of CsI, 219 mg of FAI, and 23 mg of MAI in 1 ml of a mixed solvent (DMF:DMSO = 4:1). The solution was spin-coated in a nitrogen glove box at 5000 rpm for 45 s, with an acceleration time of 5 s. After 27 s of rotation, 200 μl of chlorobenzene was added as an antisolvent, and then annealed at 115 °C for 15 min.

[0149] (6) Preparation of the passivation layer: 1 mg of PEABr was dissolved in 1 ml of isopropanol and dynamically spin-coated onto the perovskite film. The spin-coating time was 30 s and the rotation speed was 6000 rpm. After spin-coating, the sample was placed on a heating stage and annealed at 100 °C for 5 min.

[0150] (7) Preparation of electron transport layer: 10 mg PC 61 BM was dissolved in 1 ml of chlorobenzene and spin-coated onto the passivation layer for 30 seconds at 4000 rpm. After spin coating, the layer was annealed on a 100°C heating plate for 10 minutes to form the electron transport layer.

[0151] (8) Dissolve 1 mg of BCP in 1 ml of isopropanol and spin-coat it onto the electron transport layer. The spin-coating time is 30 s and the speed is 6000 rpm. After spin-coating, anneal it on a heating plate at 100 °C for 10 min.

[0152] (9) Finally, a 100 nm thick layer of Ag was deposited as the back electrode using an evaporation apparatus with silver as the thermal evaporation source at a rate of 0.5 Å / s.

[0153] The preparation method of steps (1)-(9) obtains a small-area perovskite solar cell based on an ITO / NiOx hole transport layer structure modified with a potassium chlorate intermediate layer.

[0154] Example 8:

[0155] The perovskite solar cell based on TCO / NiOx hole transport layer interface modification in this embodiment is prepared in the following process and steps:

[0156] (1) Select a 1.5 cm × 1.5 cm FTO substrate and place it in detergent, deionized water, isopropyl alcohol, and anhydrous ethanol in turn for ultrasonic treatment for 15 minutes, then place it in a 60 ° C oven for drying, and then place the cleaned conductive glass substrate in a UV-ozone device for 40 minutes.

[0157] (2) Preparation of hole transport layer: 10 nm NiO was deposited by magnetron sputtering under the following parameters: x Thin film: sputtering power 85 W, sputtering pressure 0.5 Pa, argon gas flow rate 50 sccm.

[0158] (3) Spin-coat a layer of KClO₃ aqueous solution onto the hole transport layer. Dissolve 10 mg of KClO₃ in 1 ml of ultrapure water and spin-coat it onto the treated hole transport layer for 40 seconds at a speed of 4000 rpm. After spin coating, place the sample on a heating stage and anneal at 400°C for 20 minutes.

[0159] (4) Dissolve 1 mg of Me-4PACz in 1 ml of ethanol and spin-coat it onto the treated KClO3 for 30 s at 4000 rpm. After spin-coating, place the sample on a heating stage and anneal at 100 °C for 5 min.

[0160] (5) Based on the previous step, a perovskite film was deposited by dissolving 691 mg of PbI2, 19 mg of CsI, 219 mg of FAI, and 23 mg of MAI in 1 ml of a mixed solvent (DMF:DMSO = 4:1). The solution was spin-coated in a nitrogen glove box at 5000 rpm for 45 s, with an acceleration time of 5 s. After 27 s of rotation, 200 μl of chlorobenzene was added as an antisolvent, and then annealed at 115 °C for 15 min.

[0161] (6) Preparation of the passivation layer: 1 mg of PEABr was dissolved in 1 ml of isopropanol and dynamically spin-coated onto the perovskite film. The spin-coating time was 30 s and the rotation speed was 6000 rpm. After spin-coating, the sample was placed on a heating stage and annealed at 100 °C for 5 min.

[0162] (7) Preparation of electron transport layer: 10 mg PC 61 BM was dissolved in 1 ml of chlorobenzene and spin-coated onto the passivation layer for 30 seconds at 4000 rpm. After spin coating, the layer was annealed on a 100°C heating plate for 10 minutes to form the electron transport layer.

[0163] (8) Dissolve 1 mg of BCP in 1 ml of isopropanol and spin-coat it onto the electron transport layer. The spin-coating time is 30 s and the speed is 6000 rpm. After spin-coating, anneal it on a heating plate at 100 °C for 10 min.

[0164] (9) Finally, a 100 nm thick layer of Ag was deposited as the back electrode using an evaporation apparatus with silver as the thermal evaporation source at a rate of 0.5 Å / s.

[0165] The preparation method of steps (1)-(9) obtains a small-area perovskite solar cell based on an ITO / NiOx hole transport layer structure modified with a potassium chlorate intermediate layer.

[0166] Test results:

[0167] The performance of the solar cells prepared in the above comparative examples and embodiments was tested under standard test conditions (AM1.5, 25°C, 1000W / m 2 ), and tested its open circuit voltage, short circuit current, fill factor, and cell conversion efficiency photovoltaic performance parameters. The test results are shown in Table 1.

[0168]

[0169] As can be seen from Table 1, the performance of the perovskite solar cell obtained by potassium chlorate treatment optimization is significantly improved, especially the improvement of the current density and fill factor of the battery is more obvious. In Example 2, the battery efficiency obtained by adding potassium chlorate reaches 23.89%.

[0170] Figure 1 Schematic diagram of the structure of the perovskite battery in the present invention (pin structure); Figure 2 The left picture is an SEM image of an ITO substrate, and the right picture is an SEM image of a layer of material deposited on ITO; Figure 3 The XRD curves of ITO as substrate and a layer of material deposited on ITO are shown in the figure. It can be seen from the figure that the characteristic peak of the (002) crystal plane of potassium chlorate appears at around 27°. Figure 2 and Figure 3 It can be proved that this substance is potassium chlorate. Figure 4 NiO obtained in Comparative Example 1 and Example 2 x From the XRD curve of the film, it can be seen that the characteristic peak of NiOx (200) crystal plane appears at around 43°, and the characteristic peak of NiOx is significantly enhanced after potassium chlorate treatment. Figure 5 NiO obtained in Comparative Example 1 and Example 2 xThe SEM image of the film shows that the NiOx grain size after potassium chlorate treatment is larger than that of the untreated sample. This indicates that potassium chlorate treatment promotes the growth of NiOx grains and improves the crystallinity of the film. Figure 6 and Figure 7 The JV curves of the perovskite solar cells obtained in the embodiment and the comparative example are shown in FIG. It can be seen from the figure that the current density of the embodiment is significantly improved, which indicates that the photoelectric conversion efficiency of the perovskite solar cell is significantly improved after potassium chlorate treatment.

Claims

1. A perovskite solar cell modified with a potassium chlorate intermediate layer, characterized in that: Based on PIN-type perovskite solar cells, a potassium chlorate intermediate layer is introduced between the transparent conductive substrate and the NiOx hole transport layer. Through high-temperature annealing, KClO3 undergoes thermal decomposition reaction to produce oxygen and potassium chloride, thereby improving the crystallinity and conductivity of NiOx, thereby improving the photoelectric conversion efficiency and light stability of the perovskite solar cell.

2. The perovskite solar cell according to claim 1, wherein: A KClO3 aqueous solution was spin-coated on the pretreated transparent conductive substrate, followed by magnetron sputtering deposition of NiO x The hole transport layer is subjected to high-temperature annealing after sputtering; the perovskite light absorption layer, electron transport layer and metal electrode are subsequently prepared in sequence using conventional methods.

3. The perovskite solar cell according to claim 2, wherein: The concentration of the KClO3 aqueous solution is 5-15 mg / mL.

4. The perovskite solar cell according to claim 2, wherein: When the KClO3 aqueous solution was spin-coated, the spin-coating speed was 4000 rpm and the spin-coating time was 40 s.

5. The perovskite solar cell according to claim 2, wherein: NiO deposition by magnetron sputtering x For the hole transport layer, the sputtering power was 85 W, the sputtering pressure was 0.5 Pa, and the argon gas flow rate was 50 sccm.

6. The perovskite solar cell according to claim 2, wherein: The high temperature annealing temperature is 400° C., and the annealing time is 20 min.